Strengthening Values in Islamic Educational Management Through the Spirituality of Education Practitioners - Kisbiyanto, Kisbiyanto (LPPM IAIN Kudus, 2025)
Islamic educational management continues to face challenges in integrating spiritual values into professional and sustainable institutional practices. One spiritual practice that has developed within Islamic educational environments is dalāʾil khairāt (guide to goodness), which functions not only as a religious ritual but also as a medium for shaping managerial values and character among education practitioners. This study aims to explore how Islamic education practitioners understand, experience, and implement the spiritual practice of dalāʾil khairāt to shape the values of Islamic educational management. This study employs a qualitative approach. Data were collected through in-depth interviews and document analysis involving administrators, educators, and foundation managers who actively practice dalāʾil khairāt in Kudus and its surrounding areas. The data were analyzed using thematic analysis to identify patterns of meaning and managerial values emerging from spiritual practices. The findings indicate that dalāʾil khairāt practices contribute to the development of commitment, discipline, responsibility, and integrity among Islamic educational managers. These values are reflected in more effective, accountable, and transparent institutional management. In addition, the practices strengthen practitioners’ mental resilience and emotional balance among as they carry out their managerial roles. The study suggests that integrating dalāʾil khairāt into Islamic educational management can reinforce a value-based organizational culture and support sustainable governance in Islamic educational institutions.